Measuring the Socio-economic Empowerment of Rural Households in Pakistan (Journal of Governance and Development (JGD), 2016)
This paper is developing a socio-economic empowerment index, aimed at obtaining a first snapshot of the state of socio-economic empowerment as measured by the rural household survey. Instead it is meant to foster the debate on the determinants of socio-economic empowerment and also highlights the dimensions of socio-economic empowerment. The most important section of this study is to develop an index for the measurement of socio-economic empowerment of rural households in Pakistan by using primary data of rural households which was collected through multi stage random sampling of rural households from Bahawalpur division and 600 household were interviewed for sample size. Weights of the indicator variables have been computed by using Principal Component Analysis. Socio-economic empowerment index gathers together mainly two factors, social and economic empowerment which twenty six indicators (items) grouped in eight sub-pillars and in two main pillars. Current study might be helpful for government to formulate and implement effective poverty reduction policies for rural households by enhancing socio-economic empowerment.